2010
DOI: 10.3892/ijmm_00000372
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/pAkt/p53 signaling pathway correlates with the radioresponse of non-small cell lung cancer

Abstract: Abstract.The sensitivity or resistance of cancer cells and normal tissues to ionizing radiation plays an important role in the clinical setting of lung cancer treatment. However, to date the exact molecular mechanisms of intrinsic radiosensitivity have not been well explained. In this study, we compared the radiosensitivity or radioresistance in two non-small cell lung cancers (NSCLCs), H460 and A549, and investigated the signaling pathways that confer radioresistance. H460 cells showed a significant G 2 /M ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Briefly, IR can induce PTEN accumulation to facilitate its therapeutic effects in some tumors. H460 cells obtained enhanced PTEN expression after irradiation in Il Lae Jung's previous research of nonsmall cell lung cancer (67). Similarly, the present radiation dose-dependent increase in PTEN in the IOMM-Lee cells suggests that the abovementioned mechanisms were activated during radiotherapy in meningiomas.…”
Section: Paradoxical Effects Of Ionizing Radiation On Iomm-lee Cellssupporting
confidence: 68%
“…Briefly, IR can induce PTEN accumulation to facilitate its therapeutic effects in some tumors. H460 cells obtained enhanced PTEN expression after irradiation in Il Lae Jung's previous research of nonsmall cell lung cancer (67). Similarly, the present radiation dose-dependent increase in PTEN in the IOMM-Lee cells suggests that the abovementioned mechanisms were activated during radiotherapy in meningiomas.…”
Section: Paradoxical Effects Of Ionizing Radiation On Iomm-lee Cellssupporting
confidence: 68%
“…PTEN activity is lost by mutation, deletion, or promoter methylation silencing at high frequency in many primary and metastatic human cancers 6 . A549 has a higher number of methylated CpG sites in PTEN 28 . Increased PTEN ubiquitination induced by KLHL38 may also be involved.…”
Section: Discussionmentioning
confidence: 97%
“…The inhibition of Akt associating with p53 activation and down-regulation of anti-apoptosis have been well recognized [ 36 38 , 92 ]. It has been reported that p-Akt restrains the expression of p53 in human lung cancer cells [ 93 ]. Correspondently, the augmentation of p53 level in human lung cancer cells presented in this study might be a consequence of the suppressive activity of norcycloartocarpin on p-Akt/Akt signalling ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%